Prognostic factors of pediatric ependymomas at a National Cancer Reference Center in Peru - Perez-Roca, Eduardo; Negreiros, Tatiana; Casavilca-Zambrano, Sandro; Ojeda-Medina, Luis; Díaz-Coronado, Rosdali (Frontiers in Oncology, 2024)
Background: Ependymomas are central nervous system tumors that significantly impact the quality of life and carry a high mortality rate. Both the disease itself and its treatment cause significant morbidity. At a national level in Peru, there are no reports on clinical characteristics of the disease. Methods: This retrospective study captured patient aged less than 19 years with a diagnosis of ependymoma from 2012 to 2022 at a tertiary center in Lima. Results: 85 patients were included with a median follow-up time was 51.6 months. The 5-year overall survival and progression-free survival were 55.89% (95% CI: 44.28 – 65.99) and 37.71% (95% CI: 26,21-49,16) respectively. The main prognostic factors identified were completed treatment (p=0.019), adjuvant chemotherapy (p=0.048), presence of metastasis (p=0.012), and disease recurrence (p=0.02). Conclusions: The survival of patients with ependymoma is below that reported in high-income countries. Incomplete treatment and treatment abandonment are factors that negatively impact the prognosis. Further studies are needed to identify barriers in the referral and treatment process for patients with ependymoma.